Community Perceptions on the Development of Indah Beach Marine Ecotourism Activities in Tanjung Aru Village, Sebatik Timur District, Nunukan Regency, North Kalimantan Province - Nurfatwa, Ismi; Saleha, Qoriah; Erwiantono, Erwiantono (Jurnal Perikanan dan Kelautan, 2024)
Understanding community perceptions can help to minimize resistance and, on the other side, can maximize community participation in marine ecotourism management. High community support is the key to successful development of marine ecotourism activities. The purpose of this study was to determine the public's perception of the development of marine ecotourism activities at Indah Beach, Tanjung Aru Village, based on the indicators of the Ministry of Tourism. Primary data was taken in August 2023; research and data collection methods used case studies and purposive sampling techniques with a sample size of 30 respondents. The data were analyzed using descriptive statistical methods and a Likert measurement scale. The results showed that people's perceptions of the development of marine ecotourism activities at Pantai Indah based on five ecotourism principles with a score of 79.76, which is in the range of 51.31 - 80.60 with the criteria "Moderate," which means that in general the community Agrees with what is being done by the management of Pantai Indah towards the development of marine ecotourism activities in Tanjung Aru Village. The community considers that the capacity in the Indah Beach environment has been considered and managed following acceptable limits in nature and socio-culture, has adequate public facilities, and has homestays for lodging with feasibility standards following tourist sites